Emancipatory Social Innovation: Within and Beyond the Innovative Society - Lachapelle, Marc D. (Voluntas, 2021)
Social innovation (SI) is a promising concept that has been developed and mobilized in academia, government policies, philanthropic programs, entrepreneurial projects. Scholars propose multiple conceptions and categorization of what is SI (trajectories, approaches, theoretical strands, paradigms, streams). Some recent work has also addressed the question of who is doing SI. In both cases, the what and the who remain the key characteristic of SI. Two approaches are confronted: one where SI is more presented as a concept that reproduces the neoliberal–capitalist societies; a second that conceives SI as a transformative and emancipatory pathway. With this article, I contribute to the possibilities to conceive SI as performative concept. My proposition is to analyze SI as a discourse with precise performative practices and apparatus. By doing so, it allows scholars and practitioners to better reflect and identify the effects, tensions and ambivalence and possibilities of SI. Moreover, it gives us few key aspects of what might constitute an emancipatory social innovation.
Number: 5 N'AVONS PAS ACCÈS
Keywords: Innovation sociale; Université